PENGARUH BI RATE, INFLASI DAN PERTUMBUHAN PENDAPATAN DOMESTIK BRUTO (PDB) TERHADAP YIELD SURAT UTANG NEGARA (SUN) PERIODE 2010:07-2015:12 - Debora Yuliana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research aimed to find out the impact of BI Rate, inflation and Gross Domestic Product (GDP) growth to the yield of Surat Utang Negara (SUN). The method of data analysis was multiple regression models and used secondary data quarterly period July 2010 to December 2015.The results showed that BI Rate, inflation and GDP growth significantly have a positive effect on the yield of SUN. While coefficient determination equals to 0.7727, itmeans 77.27% of yield explainable by independent variables used in this research and the rest (22.73%) explained by other factors.Keywords: Yield of SUN, BI rate, inflation, GDP growth, multiple regression.